Invasive Widow Spiders Perform Differently at Low Temperatures from Conspecifics from the Native Range. (1st June 2022) - Mowery, Monica A; Anthony, Susan E; Dorison, Alexandra N; Mason, Andrew C; Andrade, Maydianne C B
Abstract: Temperature challenges are one of the leading abiotic causes of success or failure of non-native species in a novel environment, and this is particularly true for low temperatures. Establishing and reproducing in a novel thermal environment can alter survival, behavior, and traits related to fitness. It has been proposed that plasticity or adaptation of thermal tolerance may allow an introduced species to thrive, or that successful invaders may be those with a thermal breadth in their native habitat that encompasses their new environment. Here, we tested these hypotheses using native and invasive populations of Australian redback spiders ( Latrodectus hasselti ). We measured how exposure to temperatures common to invasive and native range habitats (exposure to 15 and 25°C, respectively) affected behavioral and life-history traits and trade-offs that may underlie fitness in an invasive population detected in 1995 in Japan and a native population from Australia. We found that the critical thermal minimum ( CT min ) was higher in the invasive population from Japan than in the native population, but critical thermal maximum ( CT max ) did not differ between populations. Compared to the invasive population, eggs from the native population had a longer development time and lower hatching success at 15°C. Both populations performed equally well at 25°C, as measured by egg development time and hatching success. Invasive juveniles tested at 15°C were faster to explore a novel environment and bolder compared to those tested at 25°C. In comparison, the native population showed faster average exploration, with no differences in boldness or exploration at the two development or testing temperatures. Overall, L. hasselti from Japan maintained hatching success and development across a wider temperature range than the native population, indicating greater thermal breadth and higher behavioral plasticity. These results support the importance of plasticity in thermal tolerance and behavior for a successful invasion under novel environmental temperatures.